Anti-cardiolipin antibodies induce pregnancy failure by impairing embryonic implantation. - Sthoeger, Z M (1993)
The antiphospholipid syndrome is characterized by thrombocytopenia, thrombosis, and recurrent fetal loss in association with anti-cardiolipin antibodies (ACAs) or lupus anti-coagulants. However, the causal role of these antibodies in the disease and the mechanisms by which the ACA may induce the syndrome are not clear. Recently, we have established an experimental mouse antiphospholipid syndrome induced by the mouse IgM monoclonal ACA designated 2C4C2. In the present study, we focused on the effects of immunization with the monoclonal ACA 2C4C2 on the outcome of pregnancies in BALB/c female mice. Four weeks after active immunization with the monoclonal ACA, a severe gestational failure with low pregnancy rates, low number of fetuses, and a high rate of resorptions was observed. Moreover, embryos obtained from the ACA-immunized females on day 3.5 of pregnancy were severely impaired, demonstrating developmental delay and abnormal morphology. These abnormal embryos failed also to develop in an in vitro implantation model. Furthermore, specific binding of the 2C4C2 ACA to the trophectoderm cell lineage of in vitro implanting normal embryos was observed. Thus, our studies demonstrate that the severe ACA-induced gestational failure results from an impairment of implantation and suggest that the ACA may react directly with the preimplantation embryos.